2016
DOI: 10.5755/j01.ee.27.2.14013
|View full text |Cite
|
Sign up to set email alerts
|

Trade openness, economic growth and competitiveness. The case of the Central and Eastern European Countries

Abstract: This article examines the effects of trade openness on the economic growth and competitiveness of Central and Eastern European countries (CEEs). Although CEEs are characterised by high indicators of trade openness, they show rather different trends of economic development and competitiveness. In most CEEs, trade policies are oriented towards regional trade cooperation with an explicit aim of integration in global economics. The empirical research was conducted on the basis of the panel data for 11 CEEs over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 37 publications
5
20
0
2
Order By: Relevance
“…Ben-David and Loewey in 1997 (Hoekman & Kostecki, 2009: 16) indicated the importance of trade openness for sustained increase of economic growth as essential factor in lowering poverty rate. Studies by Sachs and Warner (1995) and Pilinkiene (2016) found that open economies grew faster than closed ones. Contrary to the above, sceptics demonstrate that there is a positive relation but it is the growth that contributes to openness rather than vice versa.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Ben-David and Loewey in 1997 (Hoekman & Kostecki, 2009: 16) indicated the importance of trade openness for sustained increase of economic growth as essential factor in lowering poverty rate. Studies by Sachs and Warner (1995) and Pilinkiene (2016) found that open economies grew faster than closed ones. Contrary to the above, sceptics demonstrate that there is a positive relation but it is the growth that contributes to openness rather than vice versa.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This is the reason for advanced innovations and technologies fl ow from leading economies to followers via trade openness. Greater rate of innovation and technology absorptions promotes the raise of human resources skills and capacities (Balcerzak, 2016), which, in turn, leads to economic growth in the long run (Pilinkiene, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…slightly higher than the EU average. Hence, it is purposeful to research whether higher degree of country's competitiveness leads to lower degree of trade openness and vice versa, and to defi ne the conditions for this interrelation (Pilinkiene, 2016;Lelek, 2014).…”
Section: Economicsmentioning
confidence: 99%
“…al., 2016). Moreover, Pilinkiene (2016) shows that internationally active countries are much more productive and competitive in comparison to those producing and acting exceptionally in the local market. International trade has a positive effect on the efficiency of resource allocation and determines faster the growth of economy, which might transform into a greater factor accumulation, in particular in the countries with technology diffusion and knowledge spill overs.…”
Section: Theoretical Framework:-mentioning
confidence: 99%
“…Moreover, trade openness defined as reduction of policy barriers to international trade rather than trade intensity (Ulasan, 2012). Although trade openness is affected by such factors as the size of country, duty level, the cost of transportation or distance to trade partners, export and import volumes remain the key constituents that most precisely depict the trade openness (Pilinkiene, 2016) The classical economists view that capital movement liberalization and trade openness will increase the growth of economy and welfare after 1980s. According to Classical and Neoclassical economists, foreign trade has important contributions to the development and the foreign trade is not only an effective productivity instrument but also it is the engine of the growth.…”
Section: Theoretical Framework:-mentioning
confidence: 99%